Power line communication: The implementation in Malaysia / J.E. Jamaluddin - Jamaluddin, J.E. (2004)
Over the past years, broadband power line communication (PLC) has received great accomplishments for delivering high speed Internet access and other lP-based applications. PLC or DPL (Digital Power Line Communication) technology operates by transmitting a high frequency signal through the existing infrastructure in power distribution networks. As of today, many utility companies around the world have decided to move forward from small and large scale trials to commercial stage. In Malaysia, the nation's leading power utility company, Tenaga Nasional Berhad (TNB) under its ICT division has put their first effort to formalize PLC installation. To comply with the PLC standards, TNB is now undergoing changes and modification in experimental trial to suit both DPL and TNB equipment. TNB is then targeting higher data rates over 1Mbps. Implementation of DPL seeks consideration of selecting several parameters such as cable type, distance, noise, topology and cross bonding to ensure a stable communication channel. Hence, sensing the increasing demand for multimedia services by customer who require ease of use and speed, broadband Internet access solution over power line offers a promising future. The high data rate performance of the latest technology and advanced digital signal processing extends a practical benefit of communicating over the electrical network, not only in-building but also for access and transport (medium voltage). Moreover, low voltage (LV) power lines could be used to carry high frequency (> 1MHz) communication signals. Thus, the concept of broadband PLC is introduced. Nevertheless, unlike twisted-pair or coaxial cables, LV power lines present an extremely harsh environment for high frequency communication signals. Despite the enormous potential, there is some skepticism about the technology and its commercial viability. This is due to several technical problems and regulatory issues that are yet to be solved. This paper gives an insight to the practical implementation of PLC/DPL in Malaysia subjected to some technical considerations.